Considering Ethical Issues Affecting Patients’ Records Stored on the Cloud in South Africa - Marutha, Ngoako; Mavhandu-Mudzusi, Azwihangwisi (African Journal of Inter/Multidisciplinary Studies, 2025)
The study sought to investigate the ethical implications of patients’ medical and health records being stored on the cloud in South Africa. A literature review was conducted in this qualitative study to examine ethical implications of patients’ medical and health records being stored on the cloud in South Africa. It was found that healthcare facilities use private cloud storage, hosted by a third party, across national borders without consideration of any ethical matters. In most instances, healthcare facilities do not request consent from patients before their records are transferred to the cloud in the hands of a third party. A framework is proposed for consideration of ethical issues regarding patients’ records that may be stored on the cloud in South Africa. It is envisaged that the framework would minimise violation of ethics principles while avoiding possible litigations to health service providers or information getting misused in the hands of the third party. There are a number of ethical issues surrounding patients’ information or records produced during healthcare services rendered to patients and kept in healthcare facilities which need to be considered before seeking service for information keeping from any third party. For different reasons, including insufficient filing space and difficulty in retrieving patients’ records during healthcare services, most healthcare facilities apply the latest technologies such as cloud computing to which the decision eventually affect patients’ personal information. Patients’ information kept on the cloud contain personal information that may eventually affect patients’ personal life. One of the issues to be addressed by the study is obtaining patient consent before disclosing their personal information to a third party.